The Star , 28 Mei 2009 (Star Publications (Malaysia) Berhad, 2009)
Patrice Evra has threatened to fight Arsenal's Cesc Fabregas. The Manchester United defender believes the Gunners skipper attempted to injure him so he would miss yesterday's Champions League final.